Retributivism, State Misconduct, and the Criminal Process. Issue 1 (2nd January 2023) - Zimran, Adiel; Dagan, Netanel
Abstract : State agents' misconduct (SAM), such as the violations carried out by the police or prosecution, may harm an offender's rights during the criminal process in various ways. What, if anything, can retributivism, as an offense-focused theory that looks to the past, offer in response to SAM? The goal of this essay is to advance a retribution-based framework for responding to SAM within the criminal process. Two retribution-based arguments are provided. First, a retribution-based response to SAM aims to protect the legitimacy of the criminal process. Such an argument is based on how the crime and punishment connect to the moral standing of the state and that connection's meaning for the legitimacy of the trial (legitimacy-based argument). Second, a retribution-based response to SAM aims to consider the offender's side of the penal dialogue and promote a more accurate calibration of the penal suffering (compensation-based argument). Based on these arguments, the essay theorizes the legal response for SAM in US and non-US traditions through the retributive lens. The essay concludes with a call for expanding the multiple roles for retributive logic to include the actions of law-enforcement actors and addresses what that expansion means for the justice of the criminal process.